The effectiveness of a web-based Dutch parenting program to prevent overweight in children age 9-13. (13th November 2019) - Ruiter, E L M; Molleman, G R M; Fransen, G A J; van der Velden, K; Engels, R C M E
Abstract: Background: We developed a web-based parenting program for parents entitled "Making a healthy deal with your child". This e-learning program can be incorporated into existing prevention programs, thereby improving these interventions by reinforcing the role of parenting and providing parents with practical tools for use in everyday situations in order to stimulate a healthy lifestyle. Methods: The effectiveness was studied in a two-armed cluster randomized controlled trial. We recruited 548 parent-child dyads of children 9-13 years in the Netherlands who participated in an existing school-based overweight prevention program. Primary outcomes included the child's dietary and sedentary behavior, and level of physical activity. Secondary outcomes included general parenting style, specific parenting practices (set of rules, modeling, monitoring), and parental self-efficacy. Multilevel multiple regression analyses in Mplus were conducted. Results: 87% of the parent-child dyads participated in the study and 47% of the parents in the intervention group completed 2 or more episodes of the e-learning. The score that parents gave to the e-learning is a 7.Main effect analyses showed in the intention-to-treat analyses that the the parents in the intervention group have more strict rules regarding eating snacks (0.046) and children of parents in the intervention group drink more milk (p = 0.018) and less sugar sweetened beverages (p = 0.024). The completers only analyses showed that the children of parents in the intervention group eat more vegetables and fruit, drink more water and less sugar sweetened beverages, and had less screentime than the children in the control group. Conclusions: The e-learning program showed small indications to be effective. A second effectiveness study is currently being investigated. If the e-learning proves to be effective it can be easily incorporated into existing overweight prevention programs for children, as well as activities regarding Youth Health Care. Key messages: The e-learning can easily incorporated into existing overweight prevention programs for children. www.gezondeafsprakenmetjekind.nl